Endomarketing e covid-19: o estudo do caso sabin - Gomes, Keylon Pereira (Universidade Federal do Tocantins, 2022)
Covid-19 has brought transformations and social impacts never seen before, it has suddenly forced people to change their habits, daily routines have changed, physical contact should be avoided, as well as any kind of agglomeration. In response to the pandemic, many changes were and are being implemented by companies, causing important transformations in work relationships, communication and in the acceleration of digitalization. In this sense, the objective of this study was to present how endomarketing was used to minimize the effects of the Covid-19 pandemic, at the Sabin laboratory. This is an exploratory and descriptive research, in which the case study was used. Primary and secondary data were collected, the first being carried out with Sabin's internal communication coordinator, through a semi-structured interview, while the secondary data were: reports, interviews, presentations and the website itself; all public domain materials, in addition to those provided, with authorization, by the company itself. The results showed that the organization already had a well-structured internal marketing sector even before the pandemic. Therefore, they already used internal communication tools and endomarketing strategies. Among the changes that took place in the face of the Covid-19 pandemic, it was identified that the biggest challenge was ignorance, changes happened very quickly, health measures were imposed and employees had to be informed. It was necessary to put employees to work from home, and there was also a virtualization of internal communication, from lives and videoconferences. Because it is an organization with humanized management, both mental and physical care of the employee was perceived. The internal marketing practices proved to be effective, being verified according to the campaign carried out. It was noted that many changes that occurred due to the pandemic will remain over time, especially the virtualization of communication.